(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Sphaerolecanium prunastri was an economically important pest of almond, apricot, and sweet chen-y, sour cherry, peach and plum in the Turkish Lake District (Afyon, Burdur and Isparta prov[nces lll Turkey) LO 1999-2001. Although there are numerous natural enemies of S. prunastri, it reached very high population densities in Afyon. Hymenopteran parasitoids recorded were: Discodes coccophagus (Ratzeburg), Microterys hortulans Erdos, Metaphycus sp. (Hym., Encyrtidae); Coccophagus lycimnia (Walker), Coccophagus sp., (ApheUnidae); Cerapterocerus mirabilis Westwood, Pachyneuron muscarum (Linnaeus) (Pteromalidae); Aprostocetus sp. (Eulophidae). Predators recorded were: Cybocephalus fodori minor Endrody-Younga (Col., Cybocephalidae); Chilochorus bipustulatus (L.), Exochomus quadripustulatus L. (Col., Coccinellidae); Calymma communirnacula (Denis & Schiffermtiller) (Lep., Noctuidae) and an unidentified species of Hemiptera (Heteroptera).